2016
DOI: 10.1111/famp.12255
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination, Internalized Homonegativity, and Attitudes Toward Children of Same‐Sex Parents: Can Secure Attachment Buffer Against Stigma Internalization?

Abstract: With increasing numbers of same-sex couples raising children in the United States, discriminatory attitudes toward children of same-sex parents (ACSSP) are of increasing concern. As with other forms of stigma and discrimination, lesbian, gay, and bisexual (LGB) individuals are at risk for internalizing these societal attitudes, which can negatively affect parenting-related decisions and behaviors and the mental and physical health of their children. Secure attachment is characterized by positive views of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 79 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…In an Italian sample of lesbian women and gay men, Pacilli et al (2011) demonstrated that high levels of ISS and political conservatism led to a more negative attitude toward same-sex parenting. Other studies (Frost 2011;Trub et al 2016) have confirmed that a high degree of ISS, low self-disclosure to family, political conservatism, and low education are positively correlated with a negative attitude toward same-sex family legalization in lesbian women and gay men. Another variable that could influence negative attitudes toward same-sex parenting is sexism since they are correlated to discriminatory and heterosexist tendencies based on the conformity to traditional gender belief systems (Lingiardi et al 2012;Whitley 2001).…”
Section: Attitudes Toward Lesbian and Gay Parenting: Gender And Sexual Orientationmentioning
confidence: 86%
See 1 more Smart Citation
“…In an Italian sample of lesbian women and gay men, Pacilli et al (2011) demonstrated that high levels of ISS and political conservatism led to a more negative attitude toward same-sex parenting. Other studies (Frost 2011;Trub et al 2016) have confirmed that a high degree of ISS, low self-disclosure to family, political conservatism, and low education are positively correlated with a negative attitude toward same-sex family legalization in lesbian women and gay men. Another variable that could influence negative attitudes toward same-sex parenting is sexism since they are correlated to discriminatory and heterosexist tendencies based on the conformity to traditional gender belief systems (Lingiardi et al 2012;Whitley 2001).…”
Section: Attitudes Toward Lesbian and Gay Parenting: Gender And Sexual Orientationmentioning
confidence: 86%
“…Studies have shown that even lesbians and gay men, like heterosexuals, may have negative attitudes toward same-sex marriage (Baiocco, Argalia, & Laghi 2012;Doyle, Rees, & Titus 2015;Egan & Sherrill 2005;Tamagawa 2016), samesex parenting, and the development of children who grow up in same-sex families Petruccelli, Baiocco, Ioverno, Pistella, & D'Urso 2015;Trub, Quinlan, Starks, & Rosenthal 2016). The majority of studies showed that greater ISS was associated with more negative attitudes toward same-sex marriage and same-sex parenting in sexual minorities (Baiocco et al 2012;Pacilli et al 2011;Trub et al 2016). In an Italian sample of 197 lesbian women and 176 gay men, Baiocco et al (2012) found that about half of the participants with a high level of ISS expressed a negative attitude toward samesex marriage.…”
Section: Attitudes Toward Lesbian and Gay Parenting: Gender And Sexual Orientationmentioning
confidence: 99%
“…Additionally, most of the adoptive parents in this sample lived in urban areas and therefore may have greater access to LG-affirming services Goldberg et al, 2013), which may explain why no significant differences emerged in stigma or homonegative microaggressions by coast (East versus West) or urbanicity (rural versus urban). Another possibility is that it is not necessarily the stigma or microaggressions per se that relate to individual health and parenting outcomes, but rather the internalization of stigma and the appraisal of microaggression experiences that may have greater impact, as supported by previous research among LG adults, including those who are parents (Goldberg and Smith, 2011;Tornello et al, 2011;Trub et al, 2017). Indeed, the roles of appraisal and internalization of stigma have been posited as among key mechanisms for how minority stress may negatively affect individual adjustment as well as interpersonal relationships (Hatzenbuehler, 2009;Prendergast and MacPhee, 2018), and experiences of stigma represent one external context that could contribute to family stress that spills over into parenting roles and family relationships (Boss et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…They are, unfortunately, also more likely to face discrimination and continued legal obstacles, types of stress that minority parents also experience (Lavner, Waterman, & Peplau, 2014). However, even when families grapple with racism and discrimination in addition to parenting challenges, parenting support contributes to their resilience (Perrin & Siegel, 2013;Trub, Quinlan, Starks, & Rosenthal, 2017).…”
Section: Competent Parenting Benefi Ts From Competent Coparentingmentioning
confidence: 99%